Characteristic studies on types of paint spray for automotive parts in small and medium industry - Jamaluddin, Mohd Fakhrul Razi (2015)
This research studied on characteristics of the conventional paint spray compared to the High Volume Low Pressure (HVLP) type of paint spray used in the automotive painting industries in terms of cost and air quality in the spray booths. Characterization of conventional and HVLP of paint spray gathered through experimental methods. Results recorded from the experiments are air pressure, air volume, paint viscosity, transfer efficiency, and overspray. The analysed results are used as parameters in the Computer Fluid Dynamics (CFD) software ANSYS CFX V.15. The simulated paint spray patterns of the conventional paint spray compared to the High Volume Low Pressure (HVLP), concurred with the findings from the experiments. At the end of this research, it concluded that HVLP has a more stable flow rate compared to the conventional spray gun. HVLP produces smaller droplet size of paint thus reducing overspray impact on hygiene and surrounding environment. HVLP recorded 77.39% transfer efficiency which was 20% more than the conventional spray gun. The spray patternation of HVLP nozzle using ANSYS CFX Version 15 simulated a full cone and symmetry spray right after the paint discharge from the nozzle. In terms of practicality, the HVLP spray gun is more suitable for coating of a car’s part in the SME compared to the conventional spray paint.